Early Infantile Epileptic Encephalopathy in an STXBP1 Patient with Lactic Acidemia and Normal Mitochondrial Respiratory Chain Function - Dong Li; Elizabeth Bhoj; Elizabeth McCormick; Fengxiang Wang; James Snyder; Tiancheng Wang; Yan Zhao; Cecilia Kim; Rosetta Chiavacci; Lifeng Tian; Marni J. Falk; Hakon Hakonarson (Case Reports in Genetics)
A wide range of clinical findings have been associated with mutations in Syntaxin Binding Protein 1 (STXBP1), including multiple forms of epilepsy, nonsyndromic intellectual disability, and movement disorders. STXBP1 mutations have recently been associated with mitochondrial pathology, although it remains unclear if this phenotype is a part of the core feature for this gene disorder. We report a 7-year-old boy who presented for diagnostic evaluation of intractable epilepsy, episodic ataxia, resting tremor, and speech regression following a period of apparently normal early development. Mild lactic acidemia was detected on one occasion at the time of an intercurrent illness. Due to the concern for mitochondrial disease, ophthalmologic evaluation was performed that revealed bilateral midperiphery pigmentary mottling. Optical coherence tomography (OCT) testing demonstrated a bilaterally thickened ganglion cell layer in the perifovea. Skeletal muscle biopsy analysis showed no mitochondrial abnormalities or respiratory chain dysfunction. Exome sequencing identified a de novo c.1651C>T (p.R551C) mutation in STXBP1. Although mitochondrial dysfunction has been reported in some individuals, our proband had only mild lactic acidemia and no skeletal muscle tissue evidence of mitochondrial disease pathology. Thus, mitochondrial dysfunction is not an obligate feature of STXBP1 disease.